2023
DOI: 10.2196/40846
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Unplanned Hospital Admissions in Multimorbid Patients Using Computational Modeling: Observational Retrospective Cohort Study

Abstract: Background Enhanced management of multimorbidity constitutes a major clinical challenge. Multimorbidity shows well-established causal relationships with the high use of health care resources and, specifically, with unplanned hospital admissions. Enhanced patient stratification is vital for achieving effectiveness through personalized postdischarge service selection. Objective The study has a 2-fold aim: (1) generation and assessment of predictive models… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…The accompanying studies on HaH-HA carried out at HCB [ 21 , 27 , 28 ] and at regional level [ 11 , 29 ] during the period have provided a comprehensive picture of the modality of care and contributed to identify future directions toward quality assurance of the service delivery. While the current report provides analytical costs for the entire population of HaH patients attended at HCB during the study period, the Triple Aim assessment done in a subset of these patients [ 27 ] confirmed health value generation of HaH-HA reporting a positive impact on patient reported outcomes and patient reported experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The accompanying studies on HaH-HA carried out at HCB [ 21 , 27 , 28 ] and at regional level [ 11 , 29 ] during the period have provided a comprehensive picture of the modality of care and contributed to identify future directions toward quality assurance of the service delivery. While the current report provides analytical costs for the entire population of HaH patients attended at HCB during the study period, the Triple Aim assessment done in a subset of these patients [ 27 ] confirmed health value generation of HaH-HA reporting a positive impact on patient reported outcomes and patient reported experience.…”
Section: Discussionmentioning
confidence: 99%
“…The OECD report [ 29 ], based on modelling of regional data, produced relevant outcomes: (i) Confirming health value generation of HaH-HA, as well as its scalability, (ii) Quantifying the potential for cost savings of HaH-HA at health system level, and (iii) Identifying high level requirements for the service deployment with emphasis on potential inequities associated to limited HaH-HA accessibility for socially vulnerable patients. Last, but not least, the two studies assessing the role of predictive modelling for selection of candidates for HaH-HA [ 21 ] and enhanced transitional care after discharge [ 28 ] pave the way toward implementation of digital tools for clinical support of service delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, MADS, or derived scores, can be integrated as part of holistic strategies for subject-specific risk assessment that combines information on various patient’s determinants of health, also known as Multisource Clinical Predictive Modelling (MCPM). The integration of MADS with other pertinent risk factors and clinical information within MCPM approaches offers a comprehensive framework for conducting risk assessments and implementing personalized interventions in the clinical arena 36,37 . This statement was grounded on the hypothesis that the implementation of comprehensive strategies for subject-specific risk prediction and stratification, incorporating multiple sources of covariates influencing patients’ health, could enhance the accuracy of predictions and facilitate informed clinical decision-making by providing reliable estimates of individual prognosis 38 .…”
Section: Discussionmentioning
confidence: 99%
“…It has become essential for informing health policy decisions, allocating resources, benchmarking, implementing preventive strategies and selecting appropriate healthcare services [1][2][3]. Likewise, in the clinical arena, HRA is a building block for generating predictive models to support clinical decision-making [4,5]. Indeed, population-based, and clinically-oriented HRA approaches are complementary elements needed to efficiently adopt integrated patientcentred care strategies.…”
Section: Background and Objectivesmentioning
confidence: 99%